In Vitro Interaction between Fluconazole and Triclosan against Clinical Isolates of Fluconazole-Resistant Candida albicans Determined by Different Methods - Yu, Lu (American Society for Microbiology, 2011)

(untitled)
The in vitro interaction between triclosan and fluconazole against 24 azole-resistant clinical isolates of Candida albicans was evaluated by the microdilution checkerboard technique. The synergisms were verified by time-killing curves and agar diffusion tests in selected strains. Antagonistic activity was not detected.